Diksi dalam Iklan Penawaran Surat Kabar Tribun Pekanbaru - Elvi Mulia Girsang; Sri Rahayu (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Section The problem in this research is how to analyze diction in bidding advertisements based on the accuracy of word choice. The purpose of this study is to describe, analyze, interpret an conclude diction according to the accuracy of word choice, and the suitability of word choice in the Pekanbaru Tribune newspaper offer advertisiment published during june 2021. The theory used is Widjono (2012), Gorys Keraf (1984),Lamuddin Finoza (1993), The source of this research data is the advertisiment of the Pekanbaru Tribune newspaper offer. This study uses a qualitative approach, this type of research is a library (Librar Research). The method. Data collection techniques. The data analysis technique in this study made a data table, the classified data was then analyzed, interpreted, concluded, the results of research on diction analysis in the advertisiment of the Pekanbaru Tribune newspaper offer. The results of the study based on the data analysis that the researchers did on the advertisiment of the Pekanbaru Tribune newspaper offer, the researchers found 16 words that were not appropriate in the choice of words. Based on the suitability of the word choice, the researcher found 21 words that were not appropriate